Solution-combustion synthesized highly luminescent CaTiO3:Gd2O3:Eu3+ perovskite nanophosphors for WLED applications - Sajesh Sasidharan; G. Jyothi; K.G. Gopchandran (Journal of Science: Advanced Materials and Devices, 2022)
A series of Ca(1-x-y)TiO3:xGd3+,yEu3+ perovskite nanophosphors were synthesized by the solution combustion employing metal-citrate complexation method. The luminescence enhancement of seven times and the color purity of 97.4% were observed when 5 mol% of Gd3+ ions were substituted in the Ca0.93TiO3:0.07Eu3+ phosphor. The occupancy of Gd3+ and Eu3+ ions at Ca2+ sites were detected by Rietveld refinements and XPS spectroscopy. The characteristic binding energy peaks of Europium and Gadolinium ions evidenced their 3+ oxidation state. Raman shifts observed for these phosphors affirmed the phase purity and the appearance of localized vibrational modes at 803 cm−1 signifying the substitution of rare earth ions in the crystal. The TEM analysis confirmed a high degree of crystallinity. The single exponential nature of the luminescence decay curves vindicated the substitution of the activator ions at a unique site. The thermal activation energy of 0.31 eV obtained for Ca0.88Gd0.05TiO3:0.07Eu3+ suggested an appreciable stability against thermal quenching due to the cross-over process. The color parameters, luminescence lifetime, Judd–Ofelt parameters and radiative properties have been fairly discussed.